Dimeric Le(a) (Le(a)-on-Le(a)) status of beta-haptoglobin in sera of colon cancer, chronic inflammatory disease and normal subjects - Park, Seung-Yeol; Yoon, Seon-Joo; Hakomori, Sen-Itiroh; Kim, Jin-Man; Kim, Ji-Yeon; Bernert, Bradford; Ullman, Thomas; Itzkowitz, Steven H; Kim, Jung Hoe (International journal of oncology, 2010)
The glycosyl epitope dimeric Lea (Lea-on-Lea), defined by mouse monoclonal antibody NCC-ST-421, was identified previously as tumor-associated antigen, expressed highly in various human cancer tissues and cell lines derived therefrom, but with minimal expression in various normal tissues. In the present study, we observed clearly higher expression of this epitope, defined by ST421, in beta-haptoglobin (beta-Hap) from sera of patients with colorectal cancer, compared to normal, healthy subjects or patients with chronic inflammatory processes (Crohn's disease, ulcerative colitis). We focused, therefore, on biochemical characterization of glycosyl epitope status expressed in beta-Hap. We concluded that the dimeric Lea epitope is carried by O-linked but not by N-linked structure, based on the following observations: i) Treatment of beta-Hap with alpha-L-fucosidase reduced its reactivity with ST421, but did not affect its reactivity with anti-Hap antibody. In contrast, treatment of purified beta-Hap with PNGase F, which releases N-linked glycans, had no effect on reactivity with ST421, but changed molecular mass from 40 kDa to 30 kDa. ii) Strong reactivity of Colo205 supernatant with ST421 was reduced clearly by pre-incubation of cells with benzyl-alpha-GalNAc.